Mechanical thrombectomy for symptomatic stent thrombosis after carotid artery stenting - Fan, You-Min; Liu, Han-Yang; Xue, Yu-Yang (Frontiers in Neurology, 2023)
Background Since there is still no consensus on the treatment of carotid stent thrombosis (CST), we would like to describe our experience with the revascularization of CST by mechanical thrombectomy. Methods We retrospectively studied patients who underwent mechanical thrombectomy after CST at Xuzhou Municipal First People's Hospital, and Xuzhou Central Hospital between January 2020 and November 2022. Results of the procedures, complications, and clinical and imaging follow-up were recorded. Results A total of 6 patients were included in this study. The stenosis grade before stent implantation was ≥85% in all patients, and the stenosis length ranged from 7-20 mm. Patients experienced CST within 6 days to 45 months after CAS, the median admission National Institutes of Health Stroke Scale (NIHSS) at CST was 12 (range 8-25).Mechanical thrombectomy was successfully performed in all patients. There was no death periprocedure, and the modified Rankin Scale (mRS) was 0-2 at the 3-month follow-up. All patients showed recovery from their neurological deficits. Conclusion Treatment of symptomatic CST with mechanical thrombectomy resulted in satisfactory clinical outcomes. This regimen could be effective and safe, and future prospective and randomized studies are warranted.